(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
This thesis provides an in-depth analysis of the methodological and pedagogical aspects of designing educational tasks based on quest technology. The study explores the theoretical foundations of quest-based learning, its psychological and didactic principles, and the methodological conditions necessary for its effective implementation. The role of quest technology in increasing students’ motivation, developing their creativity, and fostering independent and critical thinking is emphasized. Quest technology represents a modern, learner-centered approach that integrates elements of game-based and problem-based learning.